2016
DOI: 10.4283/jmag.2016.21.1.025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Deformation Temperature on Crystal Texture Formation in Hot Deformed Nanocrystalline SmCo5Permanent Magnets

Abstract: In the present study, bulk anisotropic nanocrystalline SmCo 5 magnets were prepared by hot deformation. The effect of deformation temperature on the texture and magnetic properties are presented, based on which the mechanism of plastic deformation and texture formation during the hot deformation process is discussed. Our analyses reveal that deformation temperature is one of the most important parameters that determine the texture of SmCo 5 grains. We suggest that diffusion creep plastic deformation occurs dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…[29][30][31] In fact, SmCo 5 permanent magnets can also be fabricated by hot pressing and subsequent hot deformation. In recent years, Yue [32,33] reported on hot-deformed anisotropic SmCo 5 magnets with a high coercivity over 5 T. The raw powder was prepared using a ball milling technique and the result revealed that deformation levels up to 90% lead to the formation of well-aligned platelet grains. Images of the microstructure are shown in Fig.…”
Section: Influence Of Chemical Compositionmentioning
confidence: 99%
“…[29][30][31] In fact, SmCo 5 permanent magnets can also be fabricated by hot pressing and subsequent hot deformation. In recent years, Yue [32,33] reported on hot-deformed anisotropic SmCo 5 magnets with a high coercivity over 5 T. The raw powder was prepared using a ball milling technique and the result revealed that deformation levels up to 90% lead to the formation of well-aligned platelet grains. Images of the microstructure are shown in Fig.…”
Section: Influence Of Chemical Compositionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Sm 2 Co 7 is a kind of magnet with great potential for use in high temperature environment due to its large H A (> 200 kOe) and good phase stability. [8][9][10][11][12] With the development of nanotechnology and the application of spark plasma sintering (SPS) technology in the field of nanocrystalline magnet preparation, the preparation of ultra-high coercivity (H cj ) Sm-Co bulk magnets becomes possible. [13] Preparation of Sm-Co alloy magnets by using SPS process can effectively avoid the abnormal growth of crystal grains and provide high coercivity.…”
Section: Introductionmentioning
confidence: 99%